Somatosensory evoked fields after exercise induced pain - Saloranta, Harri (2017)
The amount of research utilizing magnetoencephalography (MEG) has increased within the last few decades because of the development and better availability of equipment. With MEG, different areas of brain functionality can be studied in a variety of tasks and pathologies. Somatosensory evoked fields (SEF) are magnetic fields generated by tens of thousands of neurons firing in the primary somatosensory cortex. The purpose of this master’s thesis is to study the modulation of SEFs after exercise induced pain.